2011
DOI: 10.3801/iafss.fss.10-945
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Parameters Influencing Liquid Fuel Burning Rates

Abstract: An understanding of the mass burning rate of a fuel and the factors affecting this rate is paramount when assessing the hazards associated with a liquid fuel spill/pool scenario. To date, the vast majority of mass burning rate data originate [1,2] from liquid fuel fire scenarios where the fuel layer is ‗deep'. However, recent studies [3,4] have shown that, for thin fuel layer scenarios, the maximum mass burning rate achieved is on the order of one-fifth that presented for these ‗deep' scenarios. This study inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In these models, it is obvious that the fuel consumption due to burning is crucial in the spread process, and the quasi-steady burning is directly determined by the burning rate of the spill fire for a certain discharge rate [9]. However, the burning rate of pool fires is directly considered that of spill fires in some cases, even though this has been proved wrong by Gottuk et.al [10] and Mealy et al [11]. They found that the burning rate of spill fires is lower than that of pool fires and in some situations the ratio of the spill fires' burning rate to that of pool fires is less than 0.5.…”
Section: Introductionmentioning
confidence: 89%
“…In these models, it is obvious that the fuel consumption due to burning is crucial in the spread process, and the quasi-steady burning is directly determined by the burning rate of the spill fire for a certain discharge rate [9]. However, the burning rate of pool fires is directly considered that of spill fires in some cases, even though this has been proved wrong by Gottuk et.al [10] and Mealy et al [11]. They found that the burning rate of spill fires is lower than that of pool fires and in some situations the ratio of the spill fires' burning rate to that of pool fires is less than 0.5.…”
Section: Introductionmentioning
confidence: 89%